Diversity of materials, variety of problems. Conservation of the medieval cross-orphrey depicting the Crucifixion - Anna Gołębiowska (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The orphrey is a part of textile collection from Archdiocese’s Museum in Przemyśl (south-east of Poland). Orphrey is made in so-called relief embroidery technique and it is a typical example of late gothic embroidery.